Antithrombin III for portal vein thrombosis in patients with liver disease: A randomized, double‐blind, controlled trial. Issue 3 (7th August 2017) - Hidaka, Hisashi; Kokubu, Shigehiro; Sato, Takahiro; Katsushima, Shinji; Izumi, Namiki; Igura, Takumi; Asahara, Shingo; Notsumata, Kazuo; Osaki, Yukio; Tsuji, Keiji; Kawanaka, Hirofumi; Akahoshi, Tomohiko; et al.
Abstract : Aim: Portal vein thrombosis (PVT) is one of the most critical disorders in liver disease patients. These patients have the imbalance of coagulation and coagulation inhibition resulting from decreased levels of coagulation inhibitory factors, such as protein C, protein S, and antithrombin III (AT‐III). We designed this randomized, double‐blind, placebo‐controlled trial comparing the safety and efficacy of AT‐III for PVT in liver disease patients with those who received no treatment. Methods: Eligible patients were diagnosed with the association of thrombus, without tumor thrombus, and thrombus in more than 50% of the cross‐sectional lumen of the portal vein. Patients with 70% or less serum level of AT‐III were included. The study drug was given up to three times in a 5‐day consecutive infusion interval if the thrombus decreased in size. Efficacy was evaluated by contrast enhanced computed tomography using a five‐grade scale (complete response, partial response, slight response, no response, and progression). From October 2014 through to March 2016, 36 patients were randomly assigned to the AT‐III group and 37 patients to the placebo group. Results: The proportion of patients with complete response or partial response of PVT was significantly higher in the AT‐III group (55.6%; 20/36 patients; 95% confidence interval, 38.1–72.1) than in the placebo group (19.4%; 7/36 patients, 95% confidence interval, 8.2–36.0) ( P = 0.003). The overall incidence of adverse events and adverse drug reactions did not differ significantly between the two groups. Conclusion: Antithrombin III is one of the essential therapies for patients with PVT in cases with lower concentration levels of AT‐III.